Epidemiological survey on the identification of Leishmania spp in rodents and lizards from selected areas across the Rift Valley ecosystem, Tanzania: a pilot study (Journal of Ideas in Health, 2025)
Background: Rodents and lizards are reservoirs of various infectious pathogens including Leishmania. This study aims to understand species composition of rodents and lizards in relation to leishmaniasis.Methods: A cross-sectional study was conducted between April and May 2022. Sherman live traps were used to collect small mammals, whereas pitfall traps and hand catching were used to collect lizards. Small mammals and lizards were taxonomically identified. Spleen samples were collected separately from each specimen. Spleen impregnated smears were made on microscopic slides, fixed, and stained with 10% Giemsa stain before the cytological assay. Ecological indices were computed using paleontological statistical software.Results: A total of 303 small mammals were collected, including six rodent genera/species: Mastomys natalensis 198(65.3%); Arvicanthis spp. 73(24.1%); Rattus rattus 9 (3%); Grammomys spp. 3 (1%); Tatera spp. 2 (0.7%); Lemniscomys spp. 1 (0.3%); and one shrew, Crocidura spp. (17, 5.6%). Species diversity was significantly higher in fallow land (p=0.003) and kraal (p
Keywords: Abundance; Cytology; Diversity; Leishmania; Reservoirs; Tanzania